2002
DOI: 10.1103/physrevb.65.134416
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the anisotropic two-channel Kondo problem

Abstract: We construct and solve numerically the thermodynamic Bethe Ansatz equations for the spinanisotropic two-channel Kondo model in arbitrary external field h. At high temperatures the specific heat and the susceptibility show power law dependence. For h → 0 and at temperatures below the Kondo temperature TK a two-channel Kondo effect develops characterized by a Wilson ratio 8/3, and a logarithmic divergence of the susceptibility and the linear specific heat coefficient. Finite magnetic field, h > 0 drives the syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
6
23
0
Order By: Relevance
“…Thus, in this particular case, it is expected that the system would have a non-Fermi-liquid ͑nFL͒ ground state below the Kondo temperature T K and above the Kondo temperature, a logarithmic temperature dependence of the electrical resistance, R(T), should be observed. [3][4][5][6] The recent studies have shown that considerable T K can be achieved only outside the tunneling regime, i.e., when the first excited state is above the barrier. 7 In such a case, however, the splitting is significantly larger and hence the nFL region is harder to reach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this particular case, it is expected that the system would have a non-Fermi-liquid ͑nFL͒ ground state below the Kondo temperature T K and above the Kondo temperature, a logarithmic temperature dependence of the electrical resistance, R(T), should be observed. [3][4][5][6] The recent studies have shown that considerable T K can be achieved only outside the tunneling regime, i.e., when the first excited state is above the barrier. 7 In such a case, however, the splitting is significantly larger and hence the nFL region is harder to reach.…”
Section: Introductionmentioning
confidence: 99%
“…80. This system has a non-Fermiliquid ground state of the same type as the two-channel Kondo model (2CK) 34,40,50,67,81,82,83,84,85,86,87,88,89,90,91 . For low interimpurity exchange interaction J, the local moment screening occurs in two stages: at the higher Kondo temperature T (1) K the local moments on impurities 1 and 3 are screened, while the local moment on impurity 2 is screened at an exponentially reduced second Kondo temperature T (2) K 80,92 .…”
Section: Introductionmentioning
confidence: 99%
“…The total number of flavors ͑valleys͒ is . Further motivation to study flavors stems from the fact that in some previous studies of multiply degenerate systems, the number of flavors has not been well defined, for example heavy fermions, [27][28][29] charged domain walls, 30 a superstrong magnetic field, 2 and spin instabilities. 31,32 Cold atom systems in optical lattices [33][34][35] have a well-defined number of flavors but weak interactions between particles.…”
Section: Introductionmentioning
confidence: 99%